Desenvolvimento e avaliação de projeto de extensão universitária: promovendo o vegetarianismo em restaurantes da cidade de Santos - Silva, Mariane Bagodi Batista Da [UNIFESP] (2020)
The concern with animal welfare, environmental health and human health contributed to an increase not only in the number of vegetarians, but also for people who suffer from loss of meat consumption or who promote the market for vegetarian products. The decrease in consumption of processed animal foods concomitantly with the increase in consumption of plant foods is beneficial to the human body due to diseases caused by obesity, hypertension, type 2 diabetes mellitus, chronic kidney disease and intestinal diseases, in addition to preserving the environment. Countless restaurants adopted on your card and less one option geared to this trend. In this sense, a proposal for this work was evaluated, through interviews, or by the knowledge of customers of restaurants in Santos about the vegetarian movement, as well as if their existing requirements meet this audience. Workshops were offered in which preparations for this type of food were demonstrated, which were then subjected to sensory tests by the participants. The results of the interviews that are few are the vegetarian options offered by the restaurants that listen to the study, and the interviewees' knowledge about vegetarianism was low, however, the answers about the quality of the workshops indicated by the latter fulfilled the proposed objectives, since were well evaluated, in addition to contributing to the greater process of building knowledge and interest of the participants on the subject, demonstrating that it can be a good tool option to be used as an intervention for changes in eating habits, currently, due to the limited number of participants, makes it necessary to carry out further studies to validate the application of these actions as well as the assessment instrument.